Protective effect of the Japanese traditional medicine juzentaihoto on myelosuppression induced by the anticancer drug TS-1 and identification of a potential biomarker of this effect - Ogawa Kazuo; Omatsu Tatsushi; Matsumoto Chinami; Tsuchiya Naoko; Yamamoto Masahiro; Naito Yuji; Yoshikawa Toshikazu (BMC, 2012)
Abstract Background TS-1 is an oral anticancer drug containing a 5-fluorouracil derivative (Tegafur) that is widely used in Japan for the treatment of cancer, especially gastrointestinal tumors. Frequently, however, TS-1 therapy has to be discontinued because of leukopenia. If it were possible to predict the development of bone marrow suppression before the white blood cell (WBC) count had actually decreased, treatment could be improved by strict dosage control and/or the prophylactic administration of hematopoietic drugs. Juzentaihoto (JTT), a traditional Japanese medicine (Kampo), has been reported to activate hematopoiesis and reduce the side effects associated with chemotherapy and radiotherapy. Here, we 1) evaluate the efficacy of JTT in alleviating myelosuppression induced by TS-1 therapy in mice, and 2) explore biomarkers that reflect both induction by TS-1 and alleviation by JTT of bone marrow suppression using a proteomics approach. Methods Ten mg/kg of TS-1 was administered to Balb/c mice with or without 1 g/kg of oral JTT for 3, 5 and 7 days. WBC count and ratio of CD34+ bone marrow cells (BMCs) were estimated by flow cytometry. Plasma samples were analyzed using surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI TOF-MS). A biomarker candidate from SELDI profiling was identified using a combination of cation exchange spin column purification, SDS-PAGE, enzymatic digestion and LC-MS/MS. Results After administration of TS-1, a significant decrease in WBC count and CD34+ BMC ratio were observed at days 5 and 3, respectively. JTT treatment improved WBC count on day 7 and CD34+ BMC ratio on days 5 and 7. SELDI analysis highlighted three protein peaks that had increased on day 3 after treatment with TS-1 but remained unchanged in mice co-treated with JTT. One of the three peaks, m/z 4223.1, was further investigated and identified as a specific C-terminal fragment of albumin. Conclusion This study indicates that bone marrow suppression by treatment with TS-1 in mice might be improved by coadministration of JTT. A C-terminal fragment of albumin was identified as a candidate biomarker for predicting TS-1-induced myelosuppression. However, the sensitivity and specificity of the biomarker candidate must be validated in future clinical studies.